PENERAPAN MODEL UTAUT 2 UNTUK MENGETAHUI MINAT PENGGUNAAN APLIKASI SI-GEMBUL PADA KADER POSYANDU DI PUSKESMAS HALMAHERA SEMARANG - Melania Nur Santi; Ririn Nurmandhani; Vilda Ana Veria Setyawati; Eti Rimawati; Agung Wardoyo; Muhammad Iqbal (VISIKES: Jurnal Kesehatan Masyarakat, 2022)
SI-GEMBUL (Integrated Information System for Nutritional Status of Superior Toddlers) is an application made to collect data and handle stunting cases at Puskesmas Halmahera. Along with the increase in cases of stunting, efforts need to be made to accelerate stunting prevention in toddlers. The purpose of this study was to determine the relationship between performance expectations, business expectations, hedonistic motivation, and price value with the intention of using the SI-GEMBUL application at Puskesmas Halmahera. The type of research used in this study was quantitative research with a cross-sectional approach. The method used was the UTAUT2 method. The samples in this study were all health cadres in RW 12 and RW 14 of Rejosari Village, who were selected by purposive sampling technique. The results showed that there was a relationship between the factors of performance expectations, business expectations, hedonistic motivation, and price value to the intention to use the SI-GEMBUL application, with a significance value (sig) of 0.014 for the performance expectation variable, a significance value (sig) of 0.003 for the business expectation variable, a significance value (sig) of 0.001 for the hedonistic motivation variable, and a significance value (sig) of 0.014 for the price value variable. The advice that can be given is that health cadres can help each other using the SI-GEMBUL application and puskesmas can monitor the health cadres regarding the use of the SI-GEMBUL application so puskesmas can take advantage of the SI-GEMBUL application in the future.